What Do We Know About the Preterm Behavioral Phenotype? A Narrative Review - Fitzallen, Grace C.; Taylor, H. Gerry; Bora, Samudragupta (Frontiers in Psychiatry, 2020)
Preterm birth is associated with a significantly increased risk of childhood and adolescent psychopathology relative to full-term birth, with an inverse relationship between gestational age at birth and later risk of psychopathology. The manifestation of symptomatology and comorbidity profiles of emotional and behavioral adjustment problems in this high-risk group have been shown to be distinct from the broader pediatric population. Acknowledging these differences, a preterm behavioral phenotype has been proposed and increasingly recognized, highlighting the unique, frequent co-occurrence of symptomatology associated with attention-deficit/hyperactivity disorder, autism spectrum disorder, and anxiety disorders. The current state-of-the-art review provides a comprehensive characterization of this phenotype to date and further highlights key knowledge gaps primarily regarding the evolution of symptoms, co-occurrence of disorders and/or symptomatology within the phenotype, and associations of the phenotype with chronological age and degree of prematurity.